Holocene variations of wildfire occurrence as a guide for sustainable management of the northeastern Canadian boreal forest - Ahmed El-Guellab; Hugo Asselin; Sylvie Gauthier; Yves Bergeron; Adam A. Ali (Forest Ecosystems, 2015)
Background Cumulative impacts of wildfires and forest harvesting can cause shifts from closed-crown forest to open woodland in boreal ecosystems. To lower the probability of occurrence of such catastrophic regime shifts, forest logging must decrease when fire frequency increases, so that the combined disturbance rate does not exceed the Holocene maximum. Knowing how climate warming will affect fire regimes is thus crucial to sustainably manage the forest. This study aimed to provide a guide to determine sustainable forest harvesting levels, by reconstructing the Holocene fire history at the northern limit of commercial forestry in Quebec using charcoal particles preserved in lake sediments.